(NaNALITI^ESKOE ISSLEDOWANIE TEPLOMASSOOBMENA I TRENIQ W POGRANI^NOM SLOE (B/s - (NaGRANAT(B, (NwLADIMIR mIHAJLOWI^s; (NgRI[IN(B, (Na(B.(Nm(B.s ((NtOMSK (B:s (NiZD(B-(NWO tOM(B. (NUN(B-(NTA(B,s, 1991)
(NbIBLIOGR(B.: (NS(B. 156-170 (194 (NNAZW(B.)s
(NtOM(B. (NGOS(B. (NUN(B-(NT IM(B. (Nw(B. (Nw(B. (NkUJBY[EWAs
Keywords: (NpERENOSA QWLENIQs; (NpOGRANI^NYJ SLOJ LAMINARNYJs